Punjab State Board PSEB 7th Class Maths Book Solutions Chapter 4 Simple Equations Ex 4.2 Textbook Exercise Questions and Answers.

## PSEB Solutions for Class 7 Maths Chapter 4 Simple Equations Ex 4.2

1. Write the first step that you will use to separate the variable and then solve the equation.

Question (i).

x + 1 = 0

Answer:

Given equation x + 1 = 0

Subtracting 1 from both sides, we get

x + 1 – 1 = -1

or x = – 1

Question (ii).

x – 1 = 5

Answer:

Given equation is x – 1 = 5

Adding 1 to both sides we get

x – 1 + 1 = 5 + 1

or x = 6

Thus x = 6 is the solution of the given equation

Question (iii).

x + 6 = 2

Answer:

Given equation is x + 6 = 2

Subtracting 6 from both sides, we get:

x + 6 – 6 = 2 – 6

or x = – 4

Thus, x = – 4 is the solution of the given equation.

Question (iv).

y + 4 = 4

Answer:

Given equation is y + 4 = 4

Subtracting 4 from both sides we get

y + 4 – 4 = 4 – 4

or y = 0

Thus, y = 0 is the solution of the given equation.

Question (v).

y – 3 = 3

Answer:

Given equation is y – 3 = 3

Adding 3 to both sides we get

y – 3 + 3 = 3 + 3

or y = 6

Thus, y = 6 is the solution of the given equation.

2. Write the first step that you will use to separate the variable and then sotye the equation :

Question (i).

3x = 15

Answer:

Given equation is 3x = 15

Dividing both sides by 3 we get

\(\frac{3 x}{3}=\frac{15}{3}\)

or x = 5

Question (ii).

\(\frac{P}{7}\) = 4

Answer:

Given equation is \(\frac{P}{7}\) = 4

Multiplying both sides by 7, we get

7 × \(\frac{P}{7}\) = 7 × 4

or p = 28

Thus, p = 28 is the solution of the given equation.

Question (iii).

8y = 36

Answer:

Given equation is 8y = 36

Dividing both sides by 8, we get

\(\frac{8 y}{8}=\frac{36}{8}\)

or y = \(\frac {9}{2}\)

Question (iv).

20x = – 10

Answer:

Given equation is

20x = – 10

Dividing both sides by 20

\(\frac{20 x}{20}=\frac{-10}{20}\)

or x = \(\frac {-1}{2}\)

3. Give the steps you will use to separate the variable and then solve the equation.

Question (i).

5x + 7 = 17

Answer:

Given equation is 5x + 7 = 17

Subtracting 7 from both sides, we get

5x + 7 – 7 = 17 – 7

or 5x = 10

Dividing both sides by 5, we get

\(\frac{5 x}{5}=\frac{10}{5}\)

or x = 2

Question (ii).

\(\frac{20 x}{3}\) = 40

Answer:

Given equation is \(\frac{20 x}{3}\) = 40

Multiplying both sides by 3, we get

3 × \(\frac{20 x}{3}\) = 3 × 40

or 20x = 3 × 40

Dividing both sides by 20, we get

\(\frac{20 x}{20}\) = \(\frac{3 \times 40}{20}\)

or x = 6

Question (iii).

3p – 2 = 46

Answer:

Given equation is 3p – 2 = 46

Adding 2 to both sides, we get

3p – 2 + 2 = 46 + 2

or 3 p = 48

Dividing both sides by 3, we get:

\(\frac{3 p}{3}=\frac{48}{3}\)

or p = 16

4. Solve the following equations :

Question (i).

10x + 10 = 100

Answer:

Given equation is 10x + 10 = 100

Subtracting 10 from both sides, we get

10x + 10 – 10 = 100 – 10

or 10x = 90

Dividing both sides by 10, we get

\(\frac{10 x}{10}=\frac{90}{10}\)

or x = 9

Thus x = 9 is the solution of the given equation.

Question (ii).

\(\frac{-p}{3}\) = 5

Answer:

Given equation is \(\frac{-p}{3}\) = 5

Multiplying both sides by – 3, we get

– 3 × \(\frac{-p}{3}\) = -3 × 5

or p = -15

Thus p = – 15 is the solution of the given equation.

Question (iii).

3x + 12 = 0

Answer:

Given equation is 3x + 12 = 0

Subtracting 12 from both sides, we get

3x + 12 – 12 = – 12

or 3x = – 12

Dividing both sides by 3, we get

\(\frac{3 x}{3}=\frac{-12}{3}\)

or x = -4

Thus x = – 4 is the solution of the given equation.

Question (iv).

2q – 6 = 0

Answer:

The given equation is 2q – 6 = 0

Adding 6 to both sides, we get

2q – 6 + 6 = 0 + 6

or 2q = 6

Dividing both sides by 2, we get

\(\frac{2 q}{2}=\frac{6}{2}\)

or q = 3

Thus, q = 3 is the solution of the given equation.

Question (v).

3p = 0

Answer:

The given equation is 3p = 0

Dividing both sides by 3, we get

\(\frac{3 p}{3}=\frac{0}{3}\)

or p = 0

Thus, p = 0 is the solution of the given equation.

Question (vi).

3s = -9

Answer:

The given equation is

3s = -9

Dividing both sides by 3, we get

\(\frac{3 s}{3}=-\frac{9}{3}\)

or s = – 3

Thus, s = – 3 is the solution of the given equation.